Electronic structure of an iron porphyrin derivative on Au(1 1 1). (14th December 2018) - Stein, Arnulf; Rolf, Daniela; Lotze, Christian; Czekelius, Constantin; Franke, Katharina J; Tegeder, Petra
Abstract: Surface-bound porphyrins are promising candidates for molecular switches, electronics and spintronics. Here, we studied the structural and the electronic properties of Fe-tetra-pyridil-porphyrin adsorbed on Au(1 1 1) in the monolayer regime. We combined scanning tunneling microscopy/spectroscopy, ultraviolet photoemission, and two-photon photoemission to determine the energy levels of the frontier molecular orbitals. We also resolved an excitonic state with a binding energy of 420 meV, which allowed us to compare the electronic transport gap with the optical gap.